PENERAPAN METODE PAIRED READING/ PAIRED SUMMARIZING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MEMBACA TEKS PADA SISWA SMK ABDURRAB PEKANBARU - Neni Triana (Inteligensi : Jurnal Ilmu Pendidikan, 2019)
The purpose of this research is to know the effect of using Paired Reading/ Paired Summarizing on reading in comprehension student at SMK Abdurrab Pekanbaru, especially in Health Analysis department. This research used quasi-experimental method with pretest-posttest control group design. The total sample was 64 students who were divided into two classes, as experimental and control class. In ready ability pre-test reading ability the result showed 68.8% students were in bad category from both experimental and control classes. After conducting an experiment using the Paired Reading / Paired Summarizing learning method with the same teaching material, 12 students (35.3%) were obtained in the good category and 10 students (29.4%) in the very good category from experimental class, while the control class contained only 4 students (11.8%) and 2 students (5.9%) with the same category. The research can be concluded that using Paired Reading/Paired Summarizing on occasional student of Abdurrab Pekanbaru can increase the reading comprehension of student ability.